2020
DOI: 10.1186/s13006-020-00309-5
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent kangaroo mother care and the practice of breastfeeding late preterm infants: results from four hospitals in different provinces of China

Abstract: Background: China has an extremely low exclusive breastfeeding rate. Kangaroo mother care (KMC) has been shown to increase the exclusive breastfeeding rate among infants born extremely or very preterm. However, there is limited evidence surrounding intermittent KMC and exclusive breastfeeding in late preterm infants. In our study we investigated the association between the provision of intermittent KMC and breastfeeding practice for late preterm infants in four hospitals in different provinces of China. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
6
28
0
3
Order By: Relevance
“…Consistent with the present study, Yilmaz et al state that KMC is effective in promoting breastfeeding self-e cacy and they recommend that KMC to participate mothers in care of their infants and create a sense of empowerment in them and consequently help better development of infants [22]. Our study results are consistent with previous evidence from published literature that frequent skin-to skin contact between mother and infant is crucial to the successful transition to direct breastfeeding in preterm infants [6, 23,31] and initiation of exclusive breastfeeding in healthy full-term infants [22,23] One of the notable limitations of the present study was the small sample size of the participants in the study. Therefore, it is recommended to conduct similar studies in the coming years in different communities, and with larger sample size.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with the present study, Yilmaz et al state that KMC is effective in promoting breastfeeding self-e cacy and they recommend that KMC to participate mothers in care of their infants and create a sense of empowerment in them and consequently help better development of infants [22]. Our study results are consistent with previous evidence from published literature that frequent skin-to skin contact between mother and infant is crucial to the successful transition to direct breastfeeding in preterm infants [6, 23,31] and initiation of exclusive breastfeeding in healthy full-term infants [22,23] One of the notable limitations of the present study was the small sample size of the participants in the study. Therefore, it is recommended to conduct similar studies in the coming years in different communities, and with larger sample size.…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, the study of Zhang et al Showed mothers in the intervention group (KMC) reported more frequency and quality of breastfeeding than the control group. Therefore, it can be said that kangaroo care has signi cantly improved the number and quality of breastfeeding in mothers of premature infants [23]. Which is consistent with the present study, but in the present study, the mean score of breastfeeding self-e cacy was better in the control group (routine care with manual training) and the role-playing group A possible reason for this difference could be a difference in how is taught KMC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Late preterm infants are at a higher risk of mortality and morbidity than term infants (8) and have lower rates of breastfeeding (9). KMC could bring potential bene ts to late preterm newborns and their mothers including improved breastfeeding rates and better maternal recovery from birth-related fatigue (6,(10)(11)(12)(13)(14). The challenges of introducing, initiating and continuing kangaroo mother care on postnatal wards could differ from those faced on neonatal units with early preterm newborns.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a concurrent mixed-methods approach including quantitative maternal questionnaires and qualitative semi-structured interviews. Detailed information on our approach to quantitative and qualitative data collection has been described in other publications (5,6). The focus of the current analysis differs from our previously published papers which focused on breastfeeding and barriers and facilitators for KMC adoption.…”
Section: Methodsmentioning
confidence: 99%